Management - Hellriegel, Don.; Slocum, John W.; Jackson, Susan E. (Cincinnati, Ohio : South-Western College, 1999)
An overview of management. Managing the environment. Strategic decision making. Organizing. Leading. Controlling and evaluating.
Keywords: Management; Management